ANALISIS PAPARAN MEDIA INFORMASI DAN UANG SAKU DENGAN KONSUMSI BUAH DAN SAYUR DI SMA NEGERI 19 SURABAYA - Muzaynia, Muzaynia; Nugraheni, Fitriana; Hidayati, RR. Nurul (STIKes Mitra Keluarga, 2023)
Introduction: Low intake of fruits and vegetables among adolescents is a common problem related to adolescent consumption behaviour that can increase the risk of degenerative diseases and health problems. The study aimed to determine media exposure and pocket money with fruit and vegetable consumption at SMA Negeri 19 Surabaya. Method: The research used an quantitative observational cross-sectional with asample was 100 students selected proportionally using stratified random sampling. Result: 69% of students had adequate fruit and vegetable consumption. 32.2% of students never consume vegetables,and 36.1% of students consume fruit 1x/week. This research showed there were significant relationships between media exposure and fruit and vegetable consumption (p=0.008), however not by pocket money(p=0,289). Conclusion: School has an important role in awareness and practice of fruit and vegetable consumption among adolescents. Use of attractive information media can be used to increase consumption, so that adolescents' dietary fiber needs are met.